The End Is Not Yet : Standing Firm in Apocalyptic Times - De Gruchy, John W. (Dispatches (Minneapolis, Minn.), 2017)
The title of this book comes from Matthew's Gospel: "You will hear of wars and rumors of wars; see that you are not alarmed; for this must take place, but the end is not yet... there will be famines and earthquakes in various places: all this is but the beginning of the birth pangs." (24:6-8). This locates The End Is Not Yet within popular religious rhetoric about the "end time" and more sophisticated theological discourse on eschatology or Christian hope for a better world premised on faith in God. But is such faith still justified? And if so, how are we to describe and embody it in the life of the world? The framework of the book is the current global historical context with a particular focus on the West, and especially the political and social issues that have been highlighted by the election of Donald Trump. Among these are totalitarianism and democracy, right-wing nationalism, apocalypticism and patriotism, globalization and economic injustice, terrorism and warmongering, and political and prophetic leadership.